2002
DOI: 10.1002/em.10053
|View full text |Cite
|
Sign up to set email alerts
|

Mammary gland carcinogenesis by food‐derived heterocyclic amines: Metabolism and additional factors influencing carcinogenesis by 2‐amino‐1‐methyl‐6‐phenylimidazo[4,5‐b]pyridine (PhIP)

Abstract: The heterocyclic amines (HCAs) are a family of mutagenic/carcinogenic compounds found in cooked meats. Several HCAs are mammary gland carcinogens in rats. Of these compounds, 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) is the major one present in the human diet. This report reviews the studies on rat mammary gland carcinogenesis by HCAs; discusses what is currently known regarding mechanisms of mammary gland carcinogenesis of PhIP, especially the significance of metabolic processing; and further hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…It is significant not only because of the high concentrations relative to other HAAs, and its presence in a wide variety of foods, but also because animal studies have demonstrated the ability of PhIP to form DNA adducts that are detectable in mammary gland epithelial cells and to induce mammary tumors in rodents (38). PhIP has important tissue specificity with respect to carcinogenesis-the colon of male rats and the mammary gland and colon of female rats (9,10,38,39)-and has been associated with the same organ sites in epidemiological studies of high-meat diets and cancer (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…It is significant not only because of the high concentrations relative to other HAAs, and its presence in a wide variety of foods, but also because animal studies have demonstrated the ability of PhIP to form DNA adducts that are detectable in mammary gland epithelial cells and to induce mammary tumors in rodents (38). PhIP has important tissue specificity with respect to carcinogenesis-the colon of male rats and the mammary gland and colon of female rats (9,10,38,39)-and has been associated with the same organ sites in epidemiological studies of high-meat diets and cancer (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning humans, NOCs are present in certain processed meats, including bacon, and can be formed endogenously after consumption of red and processed meat. Many NOCs, including nitrosamines and nitrosamides, are carcinogenic in laboratory animals, since they seem to increase mammary tumors, and have been hypothesized to increase also breast cancer risk (Felton, Knize, Salmon, Malfatti, & Kulp, 2002;Ferguson, 2010;Snyderwine, 2002;Snyderwine, Venugopal, & Yu, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Even though evidence from animal studies has pointed towards a possible role of HCAs in breast carcinogenesis (3, 4), findings from previous studies on HCAs and breast cancer are inconsistent (5, 6). …”
Section: Introductionmentioning
confidence: 99%